Retrieval Accuracy Degradation in Gemini 1.5 Pro Beyond 500k-Token Contexts - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: How does the retrieval accuracy of Gemini 1.5 Pro degrade on diagram-dependent coding tasks when context length exceeds 500k tokens compared to the 100k baseline. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.3/10. This report is a machine-generated literature syn
Machine-generated literature synthesis.